2005
DOI: 10.1164/rccm.200407-887oc
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Respiratory Muscle Dysfunction in Severe Chronic Obstructive Pulmonary Disease

Abstract: This study shows that oxidative stress rather than nitric oxide is likely to be involved in the respiratory muscle dysfunction in severe COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
183
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(205 citation statements)
references
References 39 publications
14
183
2
6
Order By: Relevance
“…There is a large body of evidence, much of which is beyond the scope of this review, which supports the view that skeletal muscle dysfunction is a major contributor to exercise limitation in COPD [50][51][52][53][54]. It could therefore be hypothesised that the effects observed on muscle performance in nonanaemic athletes with EPO may also be seen in COPD patients.…”
Section: Skeletal Muscle Functionsupporting
confidence: 55%
“…There is a large body of evidence, much of which is beyond the scope of this review, which supports the view that skeletal muscle dysfunction is a major contributor to exercise limitation in COPD [50][51][52][53][54]. It could therefore be hypothesised that the effects observed on muscle performance in nonanaemic athletes with EPO may also be seen in COPD patients.…”
Section: Skeletal Muscle Functionsupporting
confidence: 55%
“…Oxidative stress may be enhanced in skeletal muscle of COPD patients as peroxidation products are elevated in the plasma of COPD patients at rest, after submaximal exercise and during exacerbations of the disease [86]. ROS can increase muscle proteolysis, inhibit muscle-specific protein expression and increase muscle cell apoptosis [87]. Skeletal muscle biopsies from COPD patients show increased protein carbonylation as evidence of increased oxidative stress [88].…”
Section: Mechanismsmentioning
confidence: 99%
“…In the hamster model of emphysema, Heunks et al (32) demonstrated an elevation in glutathione oxidation state in the diaphragms of emphysematous hamsters compared with controls that was significantly correlated to the loss of maximum specific force. Barreiro et al (2) have reported elevations in markers of oxidative stress in diaphragms of patients with severe COPD, including increased protein carbonyl formation and hydroxynonenal-protein adducts, which are related to severity of disease and/or loss of respiratory muscle strength. These findings were recently corroborated in the diaphragms of patients with severe emphysema, which identified oxidation of specific proteins, including creatine kinase and contractile and cytoskeletal proteins within the sarcomere (51).…”
Section: Evidence For Respiratory Muscle Injury Protein Degradationmentioning
confidence: 99%